Protein modelling to understand FGB mutations leading to congenital hypofibrinogenaemia. Issue 4 (17th March 2017) - Casini, A.; Vilar, R.; Beauverd, Y.; Aslan, D.; Devreese, K.; Mondelaers, V.; Alberio, L.; Gubert, C.; de Moerloose, P.; Neerman‐Arbez, M.
Abstract : Introduction: Congenital hypofibrinogenaemia is a quantitative fibrinogen disorder characterized by proportionally decreased levels of functional and antigenic fibrinogen. Mutations accounting for quantitative fibrinogen disorders are relatively frequent in the conserved COOH‐terminal globular domains of the γ and Bβ chains. The latter mutations are of particular interest since the Bβ‐chain is considered the rate‐limiting chain in the hepatic production of the fibrinogen hexamer. Aim: The aim of this study was to study the molecular pattern of four patients with congenital hypofibrinogenaemia. Methods: Four novel fibrinogen Bβ‐chain mutations leading to congenital hypofibrinogenaemia were identified in four women with heterogeneous symptoms. The human fibrinogen beta chain precursor protein sequence (P02675) was obtained from the UniProt database. The resulting models were analysed usingswisspdbviewer 4.1.0. Results: Three patients were heterozygous for different missense mutations located in the highly conserved β nodule: c.882G>C:Arg294Ser (Arg264Ser), c.1298G>T:Trp433Leu (Trp403Leu) and c.1329C>G:Asn443Lys (Asn413Lys). Modelling analyses predicted major structural modifications likely to result in impaired fibrinogen secretion. One patient was heterozygous for an intron 7 donor splice mutation (c.1244 + 1G>A), leading to the complete abolishment of the donor site. Conclusions: Protein modelling of new causative mutations and comparison of molecular, biochemical and clinical data continue to yield valuable information on the development and course of fibrinogen disorders as well as on the choice of the most appropriate treatments.